Application of response surface method and multi-objective genetic algorithm to configuration optimization of Shell-and-tube heat exchanger with fold helical baffles. (25th January 2018) - Wang, Simin; Xiao, Juan; Wang, Jiarui; Jian, Guanping; Wen, Jian; Zhang, Zaoxiao
Highlights: A novel shell-and-tube heat exchanger with fold helical baffles was proposed. Effects of helical angle and overlapped degree on performance were studied. An effective algorithm combining RSM and MOGA was adopted. Empirical correlations of the Nusselt number and friction coefficient were fitted. Abstract: A kind of shell-and-tube heat exchangers with fold baffles was proposed to eliminate the triangular leakage zones between adjacent baffles. An effective algorithm combing second-order polynomial response surface method and multi-objective genetic algorithm was adopted to study the effect of fold baffle configuration parameters on the performance of flow and heat transfer. The helical angle, overlapped degree and shell-side inlet velocity were chosen as design parameters, and the Nusselt number and shell-side pressure drop were considered as objective functions. The results show that both the Nusselt number and shell-side pressure drop increase with the decrease of helical angle and shell-side inlet velocity, and increase with the increasing overlapped degree. A set of Pareto-optimal points were obtained, and the optimization results illustrate a good agreement with CFD simulation data with the relative deviation less than ±3%. And the empirical correlations of Nusselt number and friction coefficient were obtained based on response surface method, the helical angle and overlapped degree were fitted into empirical correlations as correction factors for the first time. It is found that the adjusted coefficient of determination of the Nusselt number and friction coefficient is 0.943 and 0.999, respectively, which illustrate the fitting is correct and reliable.